2021
DOI: 10.1590/0102-33062020abb0364
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive phenology of aquatic macrophytes in the Cerrado-Pantanal ecotone

Abstract: Studies of plant phenology have been performed predominantly with terrestrial species and rarely so with aquatic communities. Such plants are fundamental for the aquatic ecosystems, representing a valuable source of resources when they are scarce in terrestrial environments for the fauna. Studies of phenology help to understand the reproduction rhythms of plant communities and provide fundamental support to management and conservation. This study aimed to describe the reproductive phenology of 15 species of aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Nevertheless, our results indicate a general trend of higher florivory levels in terrestrial plants and, specifically, a higher percentage of flowers attacked on aquatic plants during the rainy season. Flower blooming of aquatic plants in the Pantanal peaks during the rains, whereas blooming of terrestrial plants is concentrated at the end of the dry season (Damasceno‐Junior et al, 2005; Lima and Damasceno‐Junior, 2020; Simão et al, 2021). Our results for florivory seem to be in accordance with blooming peaks for each substrate, reflecting higher resource availability for florivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our results indicate a general trend of higher florivory levels in terrestrial plants and, specifically, a higher percentage of flowers attacked on aquatic plants during the rainy season. Flower blooming of aquatic plants in the Pantanal peaks during the rains, whereas blooming of terrestrial plants is concentrated at the end of the dry season (Damasceno‐Junior et al, 2005; Lima and Damasceno‐Junior, 2020; Simão et al, 2021). Our results for florivory seem to be in accordance with blooming peaks for each substrate, reflecting higher resource availability for florivores.…”
Section: Discussionmentioning
confidence: 99%
“…The Pantanal is the world's largest tropical wetland, presenting an intense environmental seasonality marked by dry and rainy seasons and a periodic flooding regime, temporal patterns that eventually determine plant species distribution, phenology, and trait selection in this ecosystem (Junk et al, 2006; Ferreira‐Júnior et al, 2016; Catian et al, 2019; Simão et al, 2021). The intensity and timing of rains and floods also create a diversity of permanently or temporarily flooded habitats, some with low flooding and others never flooded (forming an aquatic–semiaquatic–terrestrial continuum), which ultimately determine the dominance of aquatic or terrestrial plants (Adamoli, 1995; Junk et al, 2006; Scremin‐Dias et al, 2011).…”
mentioning
confidence: 99%
“…The highest density of individuals verified in SP is related to the highest abundance of L. tomentosa , which represented 26.49% of the germinated individuals in that area. This species does not have seasonal fruiting, meaning its phenophases (flowering and fruiting) last 12 months (Simão et al, 2021). Therefore, L. tomentosa constantly disperses the seeds through the wind and enriches the soil seed bank.…”
Section: Discussionmentioning
confidence: 99%
“…2e). Land use also explained phenological changes related to resource acquisition, such as modification of pH and nutrients (Toth 2018; Simao et al 2021) and fluctuations in light availability from fine particles interception (land slide, Villa et al 2020). Interestingly, we found that changing biotic interactions were reported to affect BPP phenology in six studies (Fig.…”
Section: Figmentioning
confidence: 99%